O princípio constitucional da coisa julgada em matéria tributária na República Federativa do Brasil : o novo entendimento do Supremo Tribunal Federal - Müller, Otávio Augusto Stahl (2025)
The constitutional principle of res judicata represents a fundamental guarantee of the Brazilian legal system, ensuring the stability of judicial decisions and predictability in legal relationships. In the context of Tax Law, this guarantee is even more relevant, as it directly impacts the legal certainty of taxpayers and the State's role in tax collection. The first chapter of this research focuses on defining res judicata, emphasizing its classification as a fundamental guarantee as provided in Article 5 of the Constitution. It discusses the two dimensions of res judicata: the formal aspect, which safeguards the effects of decisions within the procedural context, and the material aspect, which prevents the reexamination of already decided matters. Furthermore, it describes the regulations that protect res judicata in Brazilian law, such as those in the CRFB/88, LINDB, and CPC/15. The second chapter deepens the study of res judicata in Tax Law, highlighting taxpayers' rights, including the restitution of undue payment and protection against illegal taxation. An example of the application of res judicata in tax matters is provided, based on a ruling from the Federal Regional Court of the 4th Region. The analysis focuses on Themes 881 and 885 of General Repercussion from the Supreme Federal Court. The third chapter discusses the repercussions of the new STF decision, analyzing limitations from the ruling, reactions from the tax law community, and the impact of the precedent on taxpayers, illustrated by a hypothetical case.